“Making” Your Numbers: Engendering Organizational Control Through a Ritual of Quantification - Mazmanian, Melissa; Beckman, Christine M. (Organization Science, 2018)
Numbers such as output controls drive action in organizations, yet we know little about how key numbers are created and take on authority. Using qualitative data from multiple properties managed by a hotel management firm, we find that individuals develop and then become committed to achieving budget goals through a ritual of quantification. The budget numbers serve as output controls for the properties and employees. We find that the strength of the budget number as an undisputed future projection emerges from the ritualistic intertwining of process and normative controls in the course of producing a robust output control. Process controls delineate stages in the budgeting cycle, while normative controls (performative work and emotional investment) operate at each stage, propelling people from one stage to the next while also increasing commitment to both the process and the outcome. The result is a single reified budget number. This ritual of quantification further fosters collective solidarity and an underlying belief in the objective authority of numbers to motivate action, assess success, and drive continuous organizational growth. This work has implications for our understanding of systems of organizational control, rituals of quantification, and the microprocesses supporting the emergence of numbers seen as objective and neutral.